Motivational Patterns as an Instrument for Predicting Performance Not Only in Football? A Replication Study With Young Talented Ice Hockey Players - Zuber, Claudia; Conzelmann, Achim (Frontiers in Psychology, 2019)
In football it was recently demonstrated, that patterns of motivational constructs in young talented football players are relatively stable in early adolescence, and are associated with specific performance related outcomes (Zuber, Zibung, & Conzelmann, 2015). The aim of the present study was to check whether the motivational patterns found in youth elite football also re-emerge in ice hockey, showing similar relations to performance. 135 young male ice hockey talents (MAge = 17.26, SD = 1.24) playing on the highest and second highest level of their age group were questioned about five motivational constructs. Six months later, their coaches rated their players’ current game performance. The results demonstrated a very high similarity of the patterns in ice hockey with the ones earlier found in football. In terms of the transition to performance levels, the highly intrinsically achievement-oriented players were rated by their coaches as belonging to the top-level players significantly more often (OR = 2.6), whereas the non-achievement-oriented failure-fearing players show a higher chance to be rated as part of the lowest performance group (OR = 3.8). The results indicate the importance of achievement motivation for performance in ice hockey also, and this generalizability thus provides relevant clues which are important for consideration in national programs for talent identification across several sports.